Dilemmas of Sheltered Employment in Poland and Greece and the Concept of Supported Employment - Kobus-Ostrowska, Dorota; Papakonstantinou, Doxa (Comparative Economic Research. Central and Eastern Europe, 2021)
People with severe disabilities, such as severe mental disabilities and autism spectrum disorders, do not participate in the open, competitive labor market to the same extent as people without disabilities or other forms of disability. Sheltered employment is an internationally accepted approach for the vocational integration of people with severe disabilities, which introduces integration in sheltered workplaces mainly with other people with disabilities and ongoing support from the Government or self-government. Therefore, sheltered employment can be defined as the employment of a person with a disability under particular conditions. This paper presents the legislative framework regarding sheltered employment in Poland and Greece and the ways sheltered employment takes place in each of the two countries with the corresponding comparisons and conclusions. The results show a need for a more precise and more comprehensive legislative framework on sheltered employment in Poland and Greece. Alternative options for the vocational integration of people with severe forms of disabilities, such as supported employment programs, need to come to the fore. Supported employment seems to be the only effective and efficient way for people who have particular difficulties in finding and keeping a paid job in the open labor market to take up paid employment on an equal basis with other people. Does the concept of supported employment have a chance to prove itself on Poland and Greece’s open labor markets and become a complementary tool in the vocational activation of people with disabilities? Legislative regulations, system projects, and stable sources of financing are necessary for both countries.